(untitled) (LACCEI, 2024)
The increase in the volume of plastic consumption is a current problem and its reuse becomes necessary to care for the environment. That is why in the present work a pre-experimental investigation of a crusher for PET waste was carried out through finite element analysis using the ANSYS software. A static analysis was carried out to find deformations, stresses and a safety factor, as well as a modal analysis to find the natural frequencies and modes of vibration. Also, a complete transitory analysis was carried out to estimate the deformations, stresses and safety factors in a scenario as similar to reality as possible. The results found indicate that the first three modes of vibration, with natural frequencies of 1687 Hz, 1766.5 Hz and 1767.4 Hz, are the most critical and prone to be activated during operation. In addition, the stresses and deformations caused by dynamic loads were on average 20.12% higher than in the static regime, constituting an important variation that must be taken into account in the design of the crusher. Taking into account the results obtained, it is concluded that the design of the crusher is suitable for its subsequent manufacture, experimentation and commissioning.